2004
DOI: 10.5551/jat.11.278
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Effectively Reduces Remnants, and Small Dense LDL, and Increases HDL Particle Number in Hypertriglyceridemic Men — A Nuclear Magnetic Resonance Study

Abstract: Hypertriglyceridemia is often associated with small dense low density lipoprotein (LDL), elevated remnants, and decreased high density lipoprotein (HDL)-cholesterol (C), which comprise the dyslipidemic triad. The objective of this study was to investigate the effect of fenofibrate on the lipoprotein subfraction profile and inflammation markers in hypertriglyceridemic men. Twenty hypertriglyceridemic men were administered fenofibrate, 200 mg daily, for 8 weeks. Lipoprotein subclasses were measured by nuclear ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 35 publications
(25 reference statements)
5
41
1
4
Order By: Relevance
“…Our findings on NMR-measured lipoprotein subclasses are consistent with an earlier open-label report of fenofibrate (200 mg daily) therapy (27). Among 20 patients with severe hypertriglyceridemia (mean triglyceride levels 5.08 Ϯ 2.84 mmol/l), fasting chylomicron and large VLDL triglyceride levels were reduced (Ϫ84.0 and Ϫ65.5%, respectively), as was small LDL cholesterol (Ϫ42.0%).…”
Section: Safety Studiessupporting
confidence: 80%
“…Our findings on NMR-measured lipoprotein subclasses are consistent with an earlier open-label report of fenofibrate (200 mg daily) therapy (27). Among 20 patients with severe hypertriglyceridemia (mean triglyceride levels 5.08 Ϯ 2.84 mmol/l), fasting chylomicron and large VLDL triglyceride levels were reduced (Ϫ84.0 and Ϫ65.5%, respectively), as was small LDL cholesterol (Ϫ42.0%).…”
Section: Safety Studiessupporting
confidence: 80%
“…Several previous studies have shown that fibrate therapy increases LDL particle size. [10][11][12] In the Diabetes Atherosclerosis Intervention Study (DAIS), fenofibrate reduced the rate of coronary artery disease progression in subjects with type 2 diabetes mellitus. 13 Multivariate regression demonstrated that LDL particle size was an independent predictor of the degree of disease progression in models containing LDL-C or Apo B.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR are ligand-activated transcriptional factors and members of the nuclear hormone receptor superfamily 20,28) . Fibrates 29) and n-3 PUFA 30) are ligands of the PPAR .…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have shown that fenofibrate decreases fatty acid synthesis and increases hepatic fatty acid oxidation, thus reducing the amount of fatty acid available to triglyceride synthesis 16,17) . Fenofibrate lowers plasma triglycerides and LDL-cholesterol and raises HDLcholesterol [18][19][20] . Previous studies have reported that the lipid-lowering effects of EPA and DHA are different.…”
Section: Introductionmentioning
confidence: 99%